Neurosurgical publications in China: an analysis of the web of science database. Issue 1 (December 2015) - Liu, Weiming; Li, Deling; Ni, Ming; Jia, Wang; Wan, Weiqing; Tang, Jie; Jia, Guijun
Abstract Background Neurosurgery in China has made great progress. The aim of this study was to analyze neurosurgical publications by Chinese authors using the Web of Science database as a way to illustrate the current state of neurosurgery in China. Methods We searched the Web of Science core database for articles containing "neurosurg*" with or without an author address in "China" to obtain the set of neurosurgical publications in China and worldwide. We then extracted data from the search results to obtain information such as document type, countries/territories, organizations, publication year, title and research area. Then, we analyzed the search results of articles (document type) to generate a citation report. We identified publications by Chinese neurosurgeons that were cited more than 100 times. Results A total of 165, 365 neurosurgical publications were identified. Among them, 10, 770 were published by Chinese neurosurgeons. Chinese neurosurgical publications have increased year by year, accounting for 2 % of neurosurgical publications before 2010 and rising to 13 % from 2010 to the present. The most frequent journals for Chinese neurosurgeons differ from the most frequent journals worldwide. We identified 34 Chinese organizations that published more than 100 publications. We also identified 19 studies written by Chinese neurosurgeons that were cited more than 100 times. Basic research represents a large proportion of Chinese publications in this area, while clinical research remains a weak area. Cooperative studies were overrepresented among Chinese studies. Conclusion While China's publication output in the area of neurosurgery has made great progress, significant room for improvement remains. The next step is to strengthen Chinese neurosurgical clinical studies and improve the publishing environment for Chinese neurosurgeons.